New strategy for synthesis of hydroxyl-terminated poly(3-hexylthiophene) and its block copolymer using an η3-π-allyl hydroxyl-functionalized Ni(i) initiator. Issue 65 (1st November 2020) - Min, Xin; Zhan, Changchao; Yan, Ping; Ye, Zhigang
Abstract : A novel hydroxyl-terminated π-allyl nickel initiator is synthesized for the first time. Hydroxyl-terminated PB- b -P3HT block copolymer and hydroxyl-terminated P3HT are synthesized by using the initiator to improve the workability of P3HT. Abstract : A novel hydroxyl-terminated π-allyl nickel initiator [η 3 -Ni(CH2 CHCHCH2 OCOCH3 )][BPh F 4 ] is synthesized for the first time. 1 H-NMR analysis confirms that the Ni initiator possesses a typical π-allyl structure with a protected hydroxyl group. The Ni initiator is applied to synthesize hydroxyl-terminated poly(3-hexylthiophene). It successfully initiates the homopolymerization of thiophene, and yields narrow molecular weight distribution, hydroxyl-terminated poly(3-hexylthiophene). Moreover, it is found that [η 3 -Ni(CH2 CHCHCH2 OCOCH3 )][BPh F 4 ] has high initiating activity in the polymerization of styrene and butadiene. A hydroxyl-terminated polybutadiene- b -poly(3-hexylthiophene) block copolymer is synthesized by using [η 3 -Ni(CH2 CHCHCH2 OCOCH3 )][BPh F 4 ] to improve the workability and brittleness of poly(3-hexylthiophene).